Cutaneous amyloidosis as the first presentation of Waldenstrom macroglobulinemia - Rana Rafiei; Hojat Eftekhari; Behnam Rafiee (Babol University of Medical Sciences, 2020)
Background: Waldenstrom macroglobulinemia is a lymphoplasmacytic lymphoma with elevated serum immunoglobulin M and multi-organ involvement. Primary systemic amyloidosis usually develops due to immunoglobulin light chains depositions in different organs due to an underlying gammopathy. Case presentation: Our patient was an 86-year-old man with macroglossia, ecchymotic patches and bullous lesions associated with a skin laxity on the periorbital, palmar, and glans penis areas. Skin biopsy confirmed dermal amyloid depositions. In serum immunofixation electrophoresis, prominent monoclonal immunoglobulin-M lambda light chains were detected associated with prominent lymphoplasmacytic infiltration in bone marrow biopsy which was diagnosed as Waldenstrom macroglobulinemia. Conclusion: Skin involvement presenting as cutaneous amyloidosis could be the first manifestation of Waldenstrom macroglobulinemia. We should think about an underlying gammopathy in an old patient with skin laxity and ecchymosis.